Assessment of right ventricular function with Doppler echocardiographic indices derived from tricuspid annular motion: comparison with radionuclide angiography. (1st September 2002) - Ueti, O M; Camargo, E E; de A Ueti, A; de Lima-Filho, E C; Nogueira, E A
Abstract : Objective: To assess right ventricular systolic function using indices derived from tricuspid annular motion, and to compare the results with right ventricular ejection fraction (RVEF) calculated from radionuclide angiography. Design: Pulsed Doppler echocardiography indices were obtained from 10 patients with a normal RVEF (group 1) and from 20 patients whose RVEF was less than 45% (group 2). Results: The patients in the two groups were similar in age, systolic blood pressure, and heart rate. There was a close correlation between the tricuspid annular motion derived indices (D wave integral (DWI), peak velocity of D wave (PVDW), and tricuspid plane systolic excursion (TPSE)) and RVEF ( r = 0.72, 0.82, and 0.79, respectively). DWI was significantly higher in group 1 than in group 2. PVDW discriminated adequately between individuals with abnormal and normal right ventricular ejection fraction. The sensitivity and specificity of tricuspid annular motion derived indices were very good. Conclusions: Indices derived from tricuspid annular motion appear to be important tools for assessing right ventricular systolic function.